Tripterygium wilfordii cytochrome P450s catalyze the methyl shift and epoxidations in the biosynthesis of triptonide - Nikolaj Lervad Hansen; Louise Kjaerulff; Quinn Kalby Heck; Victor Forman; Dan Staerk; Birger Lindberg Møller; Johan Andersen-Ranberg (Nature Communications)
Abstract The diterpenoid triepoxides triptolide and triptonide from Tripterygium wilfordii (thunder god wine) exhibit unique bioactivities with potential uses in disease treatment and as a non-hormonal male contraceptives. Here, we show that cytochrome P450s (CYPs) from the CYP71BE subfamily catalyze an unprecedented 18(4→3) methyl shift required for biosynthesis of the abeo-abietane core structure present in diterpenoid triepoxides and in several other plant diterpenoids. In combination with two CYPs of the CYP82D subfamily, four CYPs from T. wilfordii are shown to constitute the minimal set of biosynthetic genes that enables triptonide biosynthesis using Nicotiana benthamiana and Saccharomyces cerevisiae as heterologous hosts. In addition, co-expression of a specific T. wilfordii cytochrome b 5 (Twcytb 5-A) increases triptonide output more than 9-fold in S. cerevisiae and affords isolation and structure elucidation by NMR spectroscopic analyses of 18 diterpenoids, providing insights into the biosynthesis of diterpenoid triepoxides. Our findings pave the way for diterpenoid triepoxide production via fermentation.